Relationship between critical thinking dispositions and critical reading skills of Malaysian ESL learners - Mohd Zin, Zuhana; Wong, Bee Eng (English Language Education Publishing, 2014)
Critical thinking disposition, an inclination (Facione, Facione & Giancarlo, 2000) or tendency (Stunipsky, Renaud, Daniels, Haynes & Perry 2008) to use critical thinking skills, is one of the essential components in critical thinking. It is posited to play a positive role in influencing one’s cognitive behaviour in thinking (Giancarlo & Facione, 2001, Smith, 1992). Therefore, a strong inclination to think critically can positively influence a reader to exercise critical thinking skills when reading critically. This study explores for the first time the relationship between the critical thinking disposition and critical reading skills of Malaysian ESL learners. A total of 374 Malaysian ESL learners participated in the study. Their dispositions were measured by the California Critical Thinking Disposition Inventory (CCTDI), an instrument that measures seven critical thinking dispositional scales: truthseeking, openmindedness, analyticity, systematicity, confidence, maturity of judgment and inquisitiveness. A self-developed critical reading comprehension test (CRCT) measured the students’ critical reading skills of evaluation and analysis. The findings showed that the level of the students’ critical thinking disposition was average with a strong disinclination on the truthseeking scale and ambivalent disinclination on the openmindedness, systematicity and maturity scales. Subsequently, the results of the CCTDI were corroborated with the analysis of the open-ended comprehension questions that measured the critical skills of analysis and evaluation. The findings indicated that, to a certain extent, their lack of dispositional attitudes, i.e., truthseeking and openmindedness, toward critical thinking were reflected in their critical reading performance. The implication from the findings of the study suggests that we should rethink critical reading instructional designs that include explicit instruction on how to foster positive critical thinking habits.